Biocompatibility of a self-assembled crosslinkable hyaluronic acid nanogel - Pedrosa, Sílvia Santos (2016)
Hyaluronic acid nanogel (HyA-AT) is a redox sensitive crosslinkable nanogel, obtained through the conjugation of a thiolated hydrophobic molecule to the hyaluronic acid chain. Engineered nanogel was studied for its biocompatibility, including immunocompatibility and hemocompatability. The nanogel did not compromise the metabolic activity or cellular membrane integrity of 3T3, microvascular endothelial cells, and RAW 264.7 cell lines, as determined by the 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide and lactate dehydrogenase release assays. Also, we didn't observe any apoptotic effect on these cell lines through the Annexin V-FITC test. Furthermore, the nanogel cell internalization was analyzed using murine bone marrow derived macrophages, and the in vivo and ex vivo biodistribution of the Cy5.5 labeled nanogel was monitored using a non-invasive near-infrared fluorescence imaging system. The HyA-AT nanogel exhibits fairly a long half-live in the blood stream, thus showing potential for drug delivery applications.